If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-4)-2(3x+4)=4(3x)+5x+4
We move all terms to the left:
3(x-4)-2(3x+4)-(4(3x)+5x+4)=0
We add all the numbers together, and all the variables
3(x-4)-2(3x+4)-(48x+4)=0
We multiply parentheses
3x-6x-(48x+4)-12-8=0
We get rid of parentheses
3x-6x-48x-4-12-8=0
We add all the numbers together, and all the variables
-51x-24=0
We move all terms containing x to the left, all other terms to the right
-51x=24
x=24/-51
x=-8/17
| 4*l−7/3=19 | | 6x-15-2x-2-4x-7=180 | | 3/6=4/y | | 2/4=3/y | | 22=10+(0.05*m) | | 2b-3=81 | | 3x62-24=0 | | 3y-1=8* | | -5.7y+4.8=0 | | 3n18=n4 | | 8(x-3+14=2(4x+5) | | X‐(x*0.1)=110 | | x+159=90 | | 8x()+30=180 | | 3(8–6p)=18p+24 | | 16=x^2-2x+1 | | 2x6.333+5+x6.333+14= | | 4s^2+4s-3=0 | | 5y–4=5y+6 | | 5y–4=5y+6 | | s/8+29=30 | | x=1.125+20/24 | | 8n+5=93 | | 120=4r(3) | | (7x-4)°=90° | | y/7+29=34 | | 8t-48=8(t- | | 1x+3=49 | | –9m+7m=–2m | | -x(-5)=-5 | | 6/7(x+1)=1/28(x+2) | | (5y–2)=48 |